Habitus and Legal Behavior in Islamic Inheritance Practice: A Socio-Legal Analysis in Rural Serang Regency, Indonesia - Taqiyuddin, Hafidz; Rusli, Rusli; Adnan, Mohammad; Alif, Muhammad (El-Usrah: Jurnal Hukum Keluarga, 2025)
This study investigates patterns of legal non-compliance in Islamic inheritance practices among rural Muslim communities in Petir District, Serang Regency, Indonesia, where the doctrinal authority of Farā’iḏ is often subordinated to customary logic and familial consensus. In many such settings, inheritance is distributed through informal arrangements that deviate from scriptural mandates, raising concerns about the erosion of Islamic legal norms and the role of religious figures in mediating these tensions. The research focuses on understanding the underlying drivers of this legal disobedience and analyzing how religious leaders respond to and interpret such practices within the community. Using a qualitative case study approach, the study draws on interviews and participant observation in two villages (Kubang Jaya and Kadugenep) and applies Bourdieu’s theory of habitus and Black’s theory of legal behavior to interpret the findings. The results show non-compliance is driven by strong customary expectations, gendered family roles, limited legal literacy, and practical constraints that hinder formal legal access. This study argues that these practices are not merely accidental or ignorant deviations but socially embedded responses to structural and normative dissonance. Religious leaders exhibit varied responses, ranging from strict textualism to pragmatic contextualization, often opting for ethical accommodation over legal enforcement. The study argues that inheritance’s legal disobedience reflects systemic social rationalities and negotiated religious authority. It contributes to ongoing discussions on Islamic legal pluralism by revealing how Farā’iḏ is accepted but selectively reconfigured to align with local moral economies and offers insight into strengthening legal literacy, religious guidance, and institutional responsiveness in Muslim-majority contexts.